Antipsychotic use among persons with schizophrenia in Sweden and Finland, trends and differences. (1st July 2021) - Taipale, Heidi; Puranen, Arto; Mittendorfer-Rutz, Ellenor; Tiihonen, Jari; Tanskanen, Antti; Cervenka, Simon; Lähteenvuo, Markku
Abstract: Objectives: To compare the differences in prevalence of antipsychotic and adjunctive pharmacotherapy use among individuals with schizophrenia between Sweden and Finland during 2006–2016. Methods: Nationwide register-based data were utilized for constructing two separate cohorts: all persons in Finland with a diagnosis of schizophrenia treated in inpatient care during 1972–2014, and persons in Sweden aged 16–64 with recorded diagnoses of schizophrenia in inpatient or specialized outpatient care, sickness absence or disability pension during 2005–2013. The prevalence of use was assessed as a point prevalence on 31 October each year 2006–2016, based on drug use periods modelled with the PRE2DUP method. In 2016, the Finnish cohort included 37, 780 persons and Swedish cohort 25, 433 persons. Results: The most commonly used antipsychotic in 2016 was oral olanzapine in both countries (22.7% [95% CI 21.6–22.4] in Finland, 20.9% [20.4–21.4] in Sweden), followed by clozapine which was more frequently used in Finland (22.0%, 21.6–22.4) than in Sweden (14.8%, 14.4–15.3). Long-acting injectable (LAI) use was almost two times more likely in Sweden (21.6%, 95% CI 21.1–22.1) than in Finland (12.8%, 12.5–13.1), a difference which was due to more common use of FG-LAIs in Sweden. A four-fold difference was observed in Z-drugs use (19.9% in Sweden versus 5.0% in Finland). Conclusion: Potential explanations for the observed discrepancies include differences in national treatment guidelines, methods of data collection, patient characteristics and/or attitudes towards treatment among both patients and physicians.